Re-use of steel slag as an aggregate to asphaltic road pavement surface. Issue 1 (1st January 2017) - Maharaj, Chris; White, Daniel; Maharaj, Rean; Morin, Cheryon
Abstract: Electric arc Furnace steel slag produced from the ferrous smelting process in the manufacture of steel in Trinidad and Tobago presents disposal and environmental challenges. Research has demonstrated the possibility of overcoming these challenges by using this waste material as a substitute for sand and limestone aggregates for road surface course construction. The chemistry of the interaction of mineral aggregates with asphaltic materials determines the mechanical properties of the mixture and its suitability for engineering applications. Since the chemistry of asphaltic materials from different sources vary the properties of the mixtures cannot be generalized. The available literature on the utilization of slag as an aggregate with Trinidad and Tobago asphaltic materials for road construction is limited. This study investigated the influence of electric arc furnace steel slag (0–20% by weight of ¾ inch sized aggregates) using the Marshall stability of blends to determine the optimal slag content. Results revealed that, a slag content of 15% by mass of ¾ inch sized aggregates (or 2.25% of the total mass of aggregate) was optimal within Marshall stability and air void acceptability. Reuse of steel slag aggregate in this manner will result improvements in pavement performance and an environmentally friendly and more efficient management of this waste materials and preservation of environment.